2014
DOI: 10.1371/journal.pone.0097200
|View full text |Cite
|
Sign up to set email alerts
|

The HER2-Encoded miR-4728-3p Regulates ESR1 through a Non-Canonical Internal Seed Interaction

Abstract: Since the early 1980s remarkable progress has been made in understanding the role of the HER2 locus in carcinogenesis, but many details of its regulatory network are still elusive. We recently reported the finding of 367 new human microRNA (miRNA) genes of which one, mir-4728, is encoded in an intron of the HER2 gene. Here, we confirm that the HER2 oncogene is a bi-functional locus encoding the membrane receptor and a functional miRNA gene. We further show that miR-4728-3p has alternative functionalities depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…For the first batch, the most enriched motifs among downregulated genes corresponded to targets of hsa-miR-4728-3p, as expected (compare Newie et al 5 and Fig. 1A).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…For the first batch, the most enriched motifs among downregulated genes corresponded to targets of hsa-miR-4728-3p, as expected (compare Newie et al 5 and Fig. 1A).…”
Section: Resultssupporting
confidence: 84%
“…During functional studies of the miRNA hsa-miR-4728-3p 5 we used several batches of the same commercially available miRNA mimic in overexpression studies in cell culture. To determine the target genes for this miRNA, we also performed microarray expression analysis and searched for differential expression between cells transfected with an hsa-miR-4728-3p mimic or a non-targeting control mimic.…”
Section: Resultsmentioning
confidence: 99%
“…MIR4728 gene is located at chr17q12 and encoded within intron 24 of the ERBB2 gene (43). Recently, Newie and colleagues demonstrated that ERBB2 amplification might lead to ESR1 downregulation through internal seed interaction with miR-4728-3p in breast cancer cells (44). We corroborate this observation identifying a positive correlation between ERBB2 and MIR4728 expression ( r = 0.90; P < 0.01) in DCIS samples in agreement with the CNV data.…”
Section: Resultsmentioning
confidence: 99%
“…To this extent, Shin et al noticed a decreased expression of miR-16, miR-21 and miR-199a-5p along with an increase in the levels of miR-92a-3p and miR-342-3p in both blood and tissue samples collected from TNBC patients [188]. Meanwhile, in HER2+ tumors, it has repeatedly been shown that miR-4728 is co-expressed with HER2, acting as an oncogene [189][190][191]. Moreover, Søkilde et al have recently demonstrated the expression of two other small RNAs in HER2-enriched tumors, namely miR-2115 and miR-7158, which are otherwise very lowly expressed in healthy tissues [192].…”
Section: Mirnas In Distinguishing Cancer Subtypesmentioning
confidence: 99%